2016
DOI: 10.3329/bjz.v44i1.30179
|View full text |Cite
|
Sign up to set email alerts
|

Infection of protozoan and Helminth parasites among the out-patients of Dhaka Medical College Hospital

Abstract: The intestinal parasites and their prevalence and intensity of infestation was investigated. A total of 793 stool samples were examined from the out patients of Dhaka medical College Hospital. Eggs and lavae of six species of intestinal parasites were recovered, of which two species were protozoans: Entamoeba histolytica Schaudinn, 1903; and Giardia intestinalis (Lambl, 1859) and four species of helminthes: Ascaris lumbricoides Linnaeus, 1758; Trichuris trichiura (Linnaeus, 1771) Stiles, 1901; Ancylostoma duod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
(6 reference statements)
2
4
0
Order By: Relevance
“…Prevalence of A. lumbricoides (23.00%) and T. trichiura (12.8%) found in the present study was similar to the findings of various studies carried out in Bangladesh from 1976 till present [13][14][15][16][17][18][19][20][21][22][23]. In contrast, mixed infection (both A. lumbricoides and T. trichiura) was much lower (3.4%) in the present study compared to the rates reported in studies conducted previously in Bangladesh [13][14][15][16][17][18][19][20][21][22][23].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Prevalence of A. lumbricoides (23.00%) and T. trichiura (12.8%) found in the present study was similar to the findings of various studies carried out in Bangladesh from 1976 till present [13][14][15][16][17][18][19][20][21][22][23]. In contrast, mixed infection (both A. lumbricoides and T. trichiura) was much lower (3.4%) in the present study compared to the rates reported in studies conducted previously in Bangladesh [13][14][15][16][17][18][19][20][21][22][23].…”
Section: Discussionsupporting
confidence: 88%
“…Khanum et al did the prevalence study in 1997, 1999 and 2005, all of which showed significant improvement from 1976, but within the nine year period (1997-2005) there was no improvement, rather deterioration was observed in both A. lumbricoides and T. trichiura prevalence rates [18][19][20]. In 2005, Uddin et al also found [21][22][23]. However, the current study have found considerable decline in the prevalence of worm infestation among rural children.…”
Section: Discussionmentioning
confidence: 99%
“…Huq and Shaikh [ 77 ] also noted that infections were higher among boys than girls. These data, and others for Bangladesh [ 78 , 79 ], suggest that infections among children up to about 4–5 years old are higher for boys with the situation reversing between genders at about adolescence. These findings might imply that the immune system of boys is either more exposed to STH during early childhood, or reflects gender differences in the response to such exposures.…”
Section: Discussionsupporting
confidence: 69%
“…Humans must realize that their health is a gift from God Almighty that they should be grateful for and guard it. Health problems can threaten anyone, regardless of differences in gender, race, and social, economic, cultural, ethnical, and religious status (8,9).…”
Section: Introductionmentioning
confidence: 99%